A Weighted Energy Efficient Clustering (WEEC) for Wireless Sensor Networks - Behboudi, N.; Abhari, A. (2011 Seventh International Conference on Mobile Ad-hoc and Sensor Networks, 2011)
Wireless sensor networks consist of hundreds or thousands of nodes and are broadly used for collecting data from the environment. In this type of network nodes communicate with each other and send their data to the base station. Since sensor nodes are battery limited, it is crucial to minimize the amount of energy they dissipate for communication. The LEACH protocol is an elegant clustering algorithm for sending information to base station. It uses clustering, therefore each node only communicates with their cluster head nodes and then those cluster heads communicate with base station. In this paper we improved the LEACH algorithm and proposed a weighted energy efficient clustering algorithm (WEEC) algorithm for wireless sensor networks. We take into consideration the location of each node while clusters are forming. The simulation result proves that our proposed scheme noticeably increases the life time of the network.